HIDDEN CURRICULUM - Fila; Kana; Mimi; Siti Nurhaliza (NETIZEN: JOURNAL OF SOCIETY AND BUSSINESS, 2024)
Hidden curriculum is an unplanned educational process that is not explicitly visible in school programs. It involves the values, norms, and behaviors learned by students through interactions with teachers, peers, and the school environment. The hidden curriculum has a significant influence in shaping students' character and attitudes. Even though it is not recorded in the official syllabus, the hidden curriculum can add value to learning, create a more democratic society, and increase student motivation and achievement. It is important for the world of education to pay attention to and utilize the hidden curriculum effectively to support a holistic and comprehensive learning process. In the hidden curriculum, there are values ​​and behaviors that are not taught explicitly to students, but influence the formation of their character. For example, when teachers ask students to do assignments independently, this tests the student's honesty value. Ironically, sometimes teachers teach lessons about honesty but indirectly allow students to cheat or collaborate with friends. The hidden curriculum has an important role in character education, but is often not documented in the formal curriculum. Barriers to implementing the hidden curriculum include differences in student character and lack of support from families. The solution involves the role of parents in forming character values ​​at home and teachers as good role models at school.